Formation of stable Si–O–C submonolayers on hydrogen-terminated silicon(111) under low-temperature conditions - Khung, Yit Lung; Ngalim, Siti Hawa; Scaccabarozzi, Andrea; Narducci, Dario (Beilstein Journal of Nanotechnology, 2015)
In this letter, we report results of a hydrosilylation carried out on bifunctional molecules by using two different approaches, namely through thermal treatment and photochemical treatment through UV irradiation. Previously, our group also demonstrated that in a mixed alkyne/alcohol solution, surface coupling is biased towards the formation of Si–O–C linkages instead of Si–C linkages, thus indirectly supporting the kinetic model of hydrogen abstraction from the Si–H surface (Khung, Y. L. et al. Chem. – Eur. J. 2014, 20, 15151–15158). To further examine the probability of this kinetic model we compare the results from reactions with bifunctional alkynes carried out under thermal treatment (<130 °C) and under UV irradiation, respectively. X-ray photoelectron spectroscopy and contact angle measurements showed that under thermal conditions, the Si–H surface predominately reacts to form Si–O–C bonds from ethynylbenzyl alcohol solution while the UV photochemical route ensures that the alcohol-based alkyne may also form Si–C bonds, thus producing a monolayer of mixed linkages. The results suggested the importance of surface radicals as well as the type of terminal group as being essential towards directing the nature of surface linkage.
Keywords: hydrogen abstraction; thermal hydrosilylation; UV-initated hydrosilylation; X-ray photoelectron spectroscopy